Domestication as the driver of lower chronic stress levels in fish in catch-and-release recreational fisheries and aquaculture versus wild conspecifics. - Ahmad Ghazal; Richard Paul; Ali Serhan Tarkan; Irmak Kurtul; Josephine Pegg; Demetra Andreou; J Robert Britton (PLoS ONE)
The manipulation of species' attributes through selective breeding can produce domesticated traits including decreased stress responses (i.e., selecting for high stress resilience). Common carp Cyprinus carpio ("carp") have been domesticated for centuries, with domesticated forms frequently used to enhance recreational catch-and-release fisheries around the world. In Atlantic salmon Salmo salar ("salmon"), two primary strains are evident, a wild strain and domesticated aquaculture strain. Here, we compared scale cortisol concentrations (a biomarker of fish chronic stress levels) between domesticated carp in catch-and-release pond fisheries and wild carp in waters with no angling. Carp of low scale cortisol concentration were apparent in all sampled populations, suggesting individuals of low stress sensitivity are encountered in both wild and domesticated strains, and in natural and captive environments. Carp with relatively high levels of scale cortisol were, however, only present in wild carp, suggesting high phenotypic variability in their chronic stress responses, with some individuals being highly sensitive to stress. In some wild carp, elevated scale cortisol concentrations could also have been indicative of adaptive responses to their heterogenous environments. We then compared wild versus farmed salmon scale cortisol levels, and found a similar pattern, with relatively high scale cortisol levels only detected in wild fish. These results indicate that while domesticated carp and salmon are exposed to potentially stressful environments, they appear to have some resilience against the adverse effects of chronic stress.